The effect of clay particles on the activity of suspended autotrophic nitrifying bacteria and on the performance of an air-lift reactor - Vieira, M. J. (2001)
Clay minerals have some properties, namely a high surface area and the ability of ion exchange that may exert some effects on microbial systems. It is often difficult to know the way the clay is exerting its influence and whether its presence improves a given metabolic process The present work concerns the study of the effect of the addition of Powdered kaolin to autotrophic nitrification systems, and includes the study of the effects of the particles on the activity of a suspended nitrifying bacteria consortium and on the performance of an air-lift biofilm reactor used for tertiary nitrification. Concerning the suspended culture, kaolin particles produced stimulation on the specific endogenous and exogenous respiration rates of the bacteria, probably due to a nutritional effect supplied by the clay. This effect was more pronounced for the ammonia oxidation rates, although nitrite oxidation was also enhanced but to a lesser extent. In respect to the presence of kaolin particles in the air-lift reactor, the results obtained indicate that the clay particles become incorporated in the biofilm pellets, but do not change significantly their thickness or their shape. However, nitrate production decreased when the concentration of particles increased. The low adsorption of ammonia by the kaolin indicated that the clay particles embedded in the biofilm did not probably retain the ions. Although it was not proved, precipitation of salts may have occurred.